Outcome of Vesico Ureteral Reflux in Children (VUR) and Idiopathic Hypercalciuria (IHC) associated with Urinary Tract Infection (UTI) in Indian Children - Dr. (Lt Col) Ashish Kumar Gupta; Kumar, Vinay; Wilson, C.G.; Tomar, R.P.S.; Sahu, Sonam (Pediatric Review: International Journal of Pediatric Research, 2020)
Background: Paediatric UTI associated with predisposing factors like VUR and IHC causes severe damage to renal tissues resulting in renal scars. Material and Methods: This prospective observational study was conducted from August 2017 to January 2019 in teaching military hospital and tertiary care corporate hospital was done to analyse and quantify the effects of these co-morbidities in Indian children with UTI. Results: A total 405 children of UTI were studied. 55 children (13.58%) had VUR being predominantly in the age group of 1-36 months (74.54%) with majority males (58.55%). 4 children (0.98%) had IHC. 346 children or 85.43% of sample size did not show any signs of VUR or IHC. 17 male children (56.66%) and 13 female children (43.33%) had bilateral VUR. Out of the 55 children with VUR, 26 (47.27%) developed renal scars. Conclusion: Medical management was successful in resolution of 27% of cases. All the 8 cases with Grade V VUR did not improve and required surgery. All the cases of IHC resolved spontaneously on conservative management.